2021
DOI: 10.1093/hmg/ddab249
|View full text |Cite
|
Sign up to set email alerts
|

A genome-first approach to rare variants in hypertrophic cardiomyopathy genes MYBPC3 and MYH7 in a medical biobank

Abstract: ‘Genome-first’ approaches to analyzing rare variants can reveal new insights into human biology and disease. Because pathogenic variants are often rare, new discovery requires aggregating rare coding variants into ‘gene burdens’ for sufficient power. However, a major challenge is deciding which variants to include in gene burden tests. Pathogenic variants in MYBPC3 and MYH7 are well-known causes of hypertrophic cardiomyopathy (HCM), and focusing on these ‘positive control’ genes in a genome-first approach coul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It was first reported by Geisterfer Lowrance et al in 1990. The MYH7 gene, as the first pathogenic gene found to be associated with hypertrophic cardiomyopathy, has been extensively reported in studies such as myocardial injury [36] . In China, the MYH7 gene mutation range is relatively widespread in patients with hypertrophic cardiomyopathy, except for E6, E7, E10, E17, E24, E25, E29 Pathogenic mutations are present in all 27 exons except for E32 and E33, with 7 mutation sites located in E22 [36,37] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first reported by Geisterfer Lowrance et al in 1990. The MYH7 gene, as the first pathogenic gene found to be associated with hypertrophic cardiomyopathy, has been extensively reported in studies such as myocardial injury [36] . In China, the MYH7 gene mutation range is relatively widespread in patients with hypertrophic cardiomyopathy, except for E6, E7, E10, E17, E24, E25, E29 Pathogenic mutations are present in all 27 exons except for E32 and E33, with 7 mutation sites located in E22 [36,37] .…”
Section: Discussionmentioning
confidence: 99%
“…The MYH7 gene, as the first pathogenic gene found to be associated with hypertrophic cardiomyopathy, has been extensively reported in studies such as myocardial injury [36] . In China, the MYH7 gene mutation range is relatively widespread in patients with hypertrophic cardiomyopathy, except for E6, E7, E10, E17, E24, E25, E29 Pathogenic mutations are present in all 27 exons except for E32 and E33, with 7 mutation sites located in E22 [36,37] . At the same time, it has been found in Western populations that the most common malignant mutations in patients with myocardial hypertrophy are associated with R403Q, R453C, R719W, and R723G mutations in the MYH7 gene [38,39] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Park et al conducted a study with a genome-first approach; the total sample size of 41,759 subjects was analyzed by whole exome sequencing (WES), and the results were then compared with their clinical data [31]. Subsequent analysis showed that only 38.5% of patients diagnosed with HCM (with a pathogenic variant in MYBPC3 or MYH7) had genetic testing performed at diagnosis.…”
Section: Sarcomere Genesmentioning
confidence: 99%
“…Subsequent analysis showed that only 38.5% of patients diagnosed with HCM (with a pathogenic variant in MYBPC3 or MYH7) had genetic testing performed at diagnosis. This means that in more than 60% of these patients, pathogenic variants could be detected by a genome-first approach [31]. It showed also the importance of evaluating novel variants in human genome research, both predicted loss-of-function (pLOF) and predicted deleterious missense (pDM) [31].…”
Section: Sarcomere Genesmentioning
confidence: 99%
“…We meta-analyzed results from gene-based group tests for rare predicted loss-of-function (pLoF) variants using SAIGE-GENE 26 (Figure 3) for 20,675 participants with and 287,123 participants without HF from the EUR population and 6,533 participants with and 62,003 participants without HF from the AFR population. Because missense variants may produce distinct consequences compared to pLoF variants 27 , we repeated the gene-based analysis, testing associations with carrier status for a predicted damaging missense variant and all-cause HF.…”
Section: Rare Variant Genetic Architecture Of All-cause Heart Failurementioning
confidence: 99%